Wind-resistant design and equivalent static wind load of base-isolated tall building: A case study. (1st June 2020) - Li, Zhihao; Huang, Guoqing; Chen, Xinzhong; Zhou, Ying; Yang, Qingshan
Highlights: A comprehensive analysis of alongwind response of a to-be-built based-isolated tall building is presented using Chinese and Japanese codes. Modeling of ESWL of base-isolated structures is discussed from the perspective of the design code. A parametric study is conducted to investigate the influence of the isolation layer stiffness and additional damping on the wind-induced response of the base-isolated building. A scheme of choosing the appropriate stiffness and additional damping is proposed for the reduction of the base shear force. These discussions and results will provide meaningful guidance to the wind-resistant design of base-isolated tall buildings, especially in China. Abstract: More base-isolated tall buildings have been constructed in earthquake- and wind-prone regions in recent years. However, less work has been done on the wind-resistant design of base-isolated tall buildings including the design of isolation system and the modeling of equivalent static wind load (ESWL), especially from the perspective of Chinese load code. This study presents a comprehensive investigation on the alongwind response of base-isolated tall building with a to-be-built tall building as an example. The dynamic wind loads specified in both Chinese and Japanese codes are used and compared. The influences of the stiffness and additional damping of the isolation layer on the modal characteristics of the base-isolated tall building are studied. The alongwind responses of fixed-base and base-isolated buildings are compared. The modeling of ESWL of base-isolated tall building is discussed. Finally, a parametric study is conducted to investigate the influence of the isolation layer stiffness and additional damping on the wind-induced response of the base-isolated building. A scheme of choosing the appropriate stiffness and additional damping is proposed for reducing the base shear force. These discussions and results will provide meaningful guidance to the wind-resistant design of base-isolated tall buildings, especially in China.